Modification and Glycation Microalgae Proteins by Non-Thermal Assisted Process - Tahra El Obeid (20487143) (2024)
Plant proteins represent a promising solution worldwide due to their low production costs and easy accessibility. Additionally, plant proteins are more environmentally sustainable. Therefore, the potential of plant proteins to meet the protein requirements as an alternative source is increasingly gaining importance. Parallel to these developments, there is a growing interest and demand in food technologies for microalgae. The main reasons for this trend include their sustainable sources not only for proteins but also for various bioactive compounds and ingredients in food technology, as well as their positive impact on carbon emissions through carbon dioxide utilization. However, despite the significant demand for algae proteins from producers and consumers, their low solubility, viscosity, texture, and aroma defects limit their usage in foods. Various modification methods and glycation applications are needed to reduce these issues. However, it is crucial that these processes result in only the targeted changes in protein structures with minimal heat and chemical usage. Non-thermal processes such as sonication, high pressure, and cold plasma can be utilized for this purpose. Additionally, two main approaches can be used for microalgae protein modification: (i) modification of algae biomass followed by protein isolation or direct use/consumption of biomass, and (ii) isolation of protein from biomass followed by subsequent modification processes. This review offers a broad perspective regarding algal proteins. Modification techniques applied to plant proteins could be beneficial in enlightening the challenges linked to the digestibility, techno-functional, and sensory attributes of algae proteins. Much more research and innovation are required to enhance the potential of algae proteins. Other Information Published in: Current Opinion in Food Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cofs.2024.101263